1996
DOI: 10.1037/0735-7044.110.5.965
|View full text |Cite
|
Sign up to set email alerts
|

Spatial learning and memory deficits after telencephalic ablation in goldfish trained in place and turn maze procedures.

Abstract: The present work investigated whether the fish telencephalon is involved in spatial learning based on place strategies in a manner similar to mammalian hippocampus. Goldfish were trained in a 4-arm maze in a room with relevant spatial cues. Sham and to-be-ablated subjects were trained in each of 4 experimental procedures designed as follows: place, turn, place-turn, and control. After acquisition, complete ablations of both telencephalic hemispheres for the experimental groups were carried out. The results sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
94
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 121 publications
(98 citation statements)
references
References 83 publications
(127 reference statements)
4
94
0
Order By: Relevance
“…The probability of at least 24/30 trials correct occurring by chance is <0.0001 and this is consistent with other studies using this method as a criterion e.g. [6]. If the fish swam to the unrewarded arm, the exit from that arm would be blocked using a removable piece of Perspex and the fish would receive a two-minute "time out" (no reward given), to mimic the amount of time the fish spent feeding before being moved back to the start arm for the next trial.…”
Section: Experimental Design Training-individualssupporting
confidence: 79%
See 1 more Smart Citation
“…The probability of at least 24/30 trials correct occurring by chance is <0.0001 and this is consistent with other studies using this method as a criterion e.g. [6]. If the fish swam to the unrewarded arm, the exit from that arm would be blocked using a removable piece of Perspex and the fish would receive a two-minute "time out" (no reward given), to mimic the amount of time the fish spent feeding before being moved back to the start arm for the next trial.…”
Section: Experimental Design Training-individualssupporting
confidence: 79%
“…Previous studies have suggested that animals can use a variety of methods to find their way through an environment [4][5][6], using two predominant mechanisms for encoding spatial locations to memory, namely egocentric and allocentric [7,8]. Allocentric encoding, so called "place learning", is thought to be more complex and cognitively demanding as it involves building up relationships between multiple features within the environment and is often synonymous with a cognitive map [6,8], although relationships between multiple features can arise through associative mechanisms [9][10][11][12][13]. On the other hand, egocentric encoding is based more on learning a particular set of responses to reach the goal, for example, learning a route and is thus often referred to as response learning [8,14].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it has been demonstrated that, as in mammals and birds, hippocampal pallium lesions in goldfish produce severe performance impairments in a variety of spatial learning tasks requiring allocentric, relational spatial memory strategies, but not when the task can be solved by means of nonrelational, egocentric strategies or nonspatial discriminations [Rodríguez et al, 2002;Broglio et al, 2010;Durán et al, 2010]. These studies show that the functional similarity between the teleost fish hippocampal pallium homologue and the hippocampus of tetrapods is striking, because it supports place learning, allocentric or worldcentered navigation [Rodríguez et al, 1994[Rodríguez et al, , 2002Durán et al, 2010], encoding of multiple allothetic spatial cues in an integrated relational memory representation [Rodríguez et al, 1994[Rodríguez et al, , 2002Salas et al, 1996b;López et al, 1999López et al, , 2000aDurán et al, 2010], conjoint encoding of the geometrical and featural properties of the environmental surfaces [Vargas et al, 2004[Vargas et al, , 2006, abilities for spatial pattern completion after partial cueing [Rodríguez et al, 1994;López et al, 1999López et al, , 2000aDurán et al, 2010], fast spatial reversal learning [Salas et al, 1996b;López et al, 2000b;Broglio et al, 2010], the capability to infer spatial relationships between elements that have never been experienced together and the flexible expression of spatial knowledge in novel situations (e.g., readily finding the shortest route to a location from a new starting place) [Salas et al, 1996a, b;Rodríguez et al, 2002] or in vector mapping [Durán et al, 2010], and even the capability of binding temporally separate events that compose sequential memories [Portavella et al, 2004;Rodríguez-Expósito et al, 2017].…”
Section: Introductionmentioning
confidence: 87%
“…Goldfish solve this task by relying on a map-like spatial memory representation that conjointly encodes the geometrical, topological, and featural characteristics of the experimental environment, forming a single, integrated spatial representation that sustains allocentric or worldcentered navigation [Salas et al, 1996b;López et al, 1999]. Therefore, the animal's performance remains unaffected by partial losses of spatial information, such as removal of a subset of the relevant cues, but is dramatically disrupted by alteration of the global configuration or geometrical features of the spatial layout [López et al, 1999].…”
Section: Dynamic Pattern Of DLV Activation Across the Stages Of Spatimentioning
confidence: 99%
“…actinopterygian) seem to be the most likely homologues of the hippocampus and amygdala of mammals (Salas et al 2006). Finally, additional relevant evidence of homologies between fish and other vertebrates can be found in a research program that is more than 10 years old (e.g., Gómez, Durán, Salas, & Rodrí-guez, 2010;Collins & Waldeck, 2006;Rodríguez, et al, 2005;Broglio et al, 2005;Durán, Vargas, Salas, & Papini, 2000;Salas, Rodríguez, Vargas, Durán & Torres, 1996;Salas, Broglio, Rodríguez, López, Portavella & Torres, 1996;Rodriguez, Duran, Vargas, Torres & Salas, 1994;Salas et al, 2006). For a recent review of this research program please refer to Salas et al (2006).…”
Section: Spatial Learningmentioning
confidence: 99%